2020
DOI: 10.1371/journal.pone.0228105
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for syndromic surveillance using veterinary necropsy reports

Abstract: The use of natural language data for animal population surveillance represents a valuable opportunity to gather information about potential disease outbreaks, emerging zoonotic diseases, or bioterrorism threats. In this study, we evaluate machine learning methods for conducting syndromic surveillance using free-text veterinary necropsy reports. We train a system to detect if a necropsy report from the Wisconsin Veterinary Diagnostic Laboratory contains evidence of gastrointestinal, respiratory, or urinary path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…AI also includes methods to mobilise information available on the web. For example, semi-automatic data mining methods enabled to identify emerging signals for international surveillance of epizooties [ 74 ] or to analyse veterinary documents such as necropsy reports [ 75 , 76 ]. Methods from the field of natural language processing can compensate the scarcity of data by extracting syntactic and semantic information from textual records, triggering alerts on new emerging threats that could have been missed otherwise.…”
Section: Revisiting Ah Case Detection Methods At Different Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…AI also includes methods to mobilise information available on the web. For example, semi-automatic data mining methods enabled to identify emerging signals for international surveillance of epizooties [ 74 ] or to analyse veterinary documents such as necropsy reports [ 75 , 76 ]. Methods from the field of natural language processing can compensate the scarcity of data by extracting syntactic and semantic information from textual records, triggering alerts on new emerging threats that could have been missed otherwise.…”
Section: Revisiting Ah Case Detection Methods At Different Scalesmentioning
confidence: 99%
“…Such research is just starting in AH [ 46 ] and must be extended as part of the development of agro-ecology, facing current societal demand for product quality and respect for ecosystems and their biodiversity on one side, animal well-being and ethics on the other side, and more generally international health security.
Figure 4 Identifying relevant strategies to control bovine paratuberculosis at a regional scale (adapted from [ 76 ] ) . Classically, identifying relevant strategies means defining them a priori and comparing them, e.g., by modelling.
…”
Section: Targeted Interventions Model Of Human Decisions and Suppormentioning
confidence: 99%
“…These studies were focused mostly on livestock (26). The temporal unit of data collection was most commonly day (17) or month (16), and the median period (years) covered by the datasets analyzed was 10 (IQR [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Literature Scanmentioning
confidence: 99%
“…All of the reports listed above applied information retrieval techniques to biomedical text pertaining to humans. In the veterinary domain, Bollig et al [2] used a machine learning based approaches for extraction of different pathologies from free text. Furrer et al [7] built a text mining tool for veterinary surveillance by linking terms identified in necropsies to existing ontologies.…”
Section: Information Retrieval In Veterinary Domainmentioning
confidence: 99%
“…The ability to effectively confirm or rule out the presence of a pathology based on descriptions of abnormalities would allow for clearer understanding of the problems facing marine mammals. Information retrieval approaches have been applied extensively in human pathology [3,8,11,21,25,26], and other animal pathologies [2,7,13], however, no work currently exists for marine mammal pathology free text.…”
Section: Introductionmentioning
confidence: 99%